2014
DOI: 10.1007/s00590-014-1571-4
|View full text |Cite
|
Sign up to set email alerts
|

Initial stability of cementless acetabular cups: press-fit and screw fixation interaction—an in vitro biomechanical study

Abstract: Background Press-fit and screw fixation are important technical factors to achieve initial stability of a cementless acetabular cup for good clinical results of total hip arthroplasty. However, how these factors affect one another in initial cup fixation remains unclear. Therefore, this study aimed to evaluate the mutual influence between press-fit and screw fixation on initial cup stability.MethodsFoam bone was subjected to exact hemispherical-shape machining to diameters of 48, 48.5 and 49 mm. A compressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 19 publications
0
35
0
1
Order By: Relevance
“…In addition to high contact forces, friction moments in the joint may endanger the fixation of acetabular cups, as demonstrated by the frequent implant failures caused by cup loosening [ 11 – 13 ]. For an under-reaming of only 1 mm, a moment of 8.8 Nm was reported to loosen cementless cups after only 5 loading cycles [ 14 ], but even values as small as 2.2 Nm have been associated with cup failures [ 15 ]. Further statistical analyses suggested that even a more substantial under-reaming of 2 mm, and a moment as little as 3.3 Nm would be sufficient to cause fixation failure in 4.6% of the subjects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high contact forces, friction moments in the joint may endanger the fixation of acetabular cups, as demonstrated by the frequent implant failures caused by cup loosening [ 11 – 13 ]. For an under-reaming of only 1 mm, a moment of 8.8 Nm was reported to loosen cementless cups after only 5 loading cycles [ 14 ], but even values as small as 2.2 Nm have been associated with cup failures [ 15 ]. Further statistical analyses suggested that even a more substantial under-reaming of 2 mm, and a moment as little as 3.3 Nm would be sufficient to cause fixation failure in 4.6% of the subjects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, the stability of cup-bone bonding was investigated in cadavers or using plastic bone substitutes. A loosening moment of 8.8 Nm was reported for cementless cups [19], but values as low as 2.2 Nm were reported [20], both with an under-reaming of 1 mm. In comparison, our own i n vivo load measurements with instrumented hip implants [21] have determined average friction moments during walking between 2.25 ±0.29 Nm (three months postoperatively) and 1.76 ±0.83 Nm (12 months postoperatively) [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In cementless press-fit cups, this initial stability is achieved by the press-fit fixation. Additional primary fixation may be obtained by the use of extra screws ( Tabata et al. 2015 ).…”
mentioning
confidence: 99%